2011
DOI: 10.5376/mpb.2011.02.0008
|View full text |Cite
|
Sign up to set email alerts
|

Integration and Expression Stability of Transgenes in Hybriding Transmission of Transgenic Rice Plants Produced by Particle Bombardment

Abstract: Four transgenic rice lines TR 5, TR 6, Ming B and Jingyin 119 obtained via particle bombardment were used as transgene donors to create hybrids. The integration and expression stability of exotic bar and cecropin B gene in conventional hybriding transmission were investigated by Southern and Northern blotting analyses. The selection marker bar gene was transferred to all hybrids under selection of Basta herbicide. Loss or gain of small hybridization bands (no more than 2.0 kb) of bar gene occurred in some hybr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Independent studies have also assessed genetic stability of GMO events not only with different approaches (e.g. cytogenetics and Southern Blot) [10, 11] but also with more rigorous criterions, such as seasonal and tissue-specific ELISA analysis [12] and RNA expression using Northern blot technique [11]. In addition, studies have detected transgene rearrangements, such as sequence deletions [1315] and nucleotide addition of undesired fragments into the transgene sequence [16], and also, alterations in mRNA expression levels were also observed [17].…”
Section: Introductionmentioning
confidence: 99%
“…Independent studies have also assessed genetic stability of GMO events not only with different approaches (e.g. cytogenetics and Southern Blot) [10, 11] but also with more rigorous criterions, such as seasonal and tissue-specific ELISA analysis [12] and RNA expression using Northern blot technique [11]. In addition, studies have detected transgene rearrangements, such as sequence deletions [1315] and nucleotide addition of undesired fragments into the transgene sequence [16], and also, alterations in mRNA expression levels were also observed [17].…”
Section: Introductionmentioning
confidence: 99%
“…On the effect of selection agent on oil palm transformation, minimal inhibitory concentration studies showed that herbicides Basta and hygromycin are the most effective selectable agents as they could kill the untransformed cells at a very low concentration (Parveez et al, 1996;. Basta and hygromycin were also shown to be the effective selection agents for other monocots such as rice (Zhao et al, 2011;Htwe et al, 2014), turfgrass (Song et al, 2013) and finger millet (Ignacimuthu and Ceasar, 2012). Initial regeneration of transgenic oil palm was obtained after transformed oil palm calli were selected on herbicide Basta.…”
Section: Introductionmentioning
confidence: 99%
“…Various ways to deliver foreign deoxyribonucleic acid (DNA) into the oil palm genome have been evaluated such as bombardment (Parveez et al, 2000;2015a), Agrobacterium-mediated transfer (Izawati et al, 2015;, Polyethylene glycol (PEG)mediated transfection and DNA microinjection (Masani et al, 2014). DNA delivery by bombardment has been widely used and proven in many plants such as soyabean (Khalafalla et al, 2005), rice (Tian et al, 2015;Zhao et al, 2011;Higuchi et al, 2001;Datta et al, 2000), wheat (Melchiorre et al, 2002) and banana (Mahdavi et al, 2014;Sreeraman et al, 2005). However, the transformation efficiency of oil palm by bombardment was low at about 1%-1.5% (Parveez, 2000).…”
Section: Introductionmentioning
confidence: 99%